2023
DOI: 10.4274/tjar.2022.221079
|View full text |Cite
|
Sign up to set email alerts
|

Pre-anaesthesia Telephone Consultation: A Safe Alternative for Anaesthesia Assessment in Case of Repeated Low or Intermediate Risk Surgeries: A Prospective Cohort Study

Abstract: Objective: Telemedicine has widely expanded during the coronavirus disease-2019 pandemic. Our objective was to evaluate the feasibility, safety, effectiveness, and satisfaction of pre-anaesthesia telephone consultation (PATC).Methods: From December 2015 to October 2016, a prospective survey was administered to anaesthesiologists, nurse anaesthetists, and patients of the ambulatory and maxillofacial departments. Patients having a pre-anaesthesia consultation (PAC) within the previous year in the department, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Literature suggests face-to-face preoperative visits for patients over 65, with significant comorbidities (e.g., diabetes), or on 7 + medications, potentially needing additional preoperative examinations after anesthesiologic evaluation [ 15 ]. Although this might suggest that patients with higher ASA score need an in-person visit, some authors found no significant differences in the rate of procedure cancellation among patients with ASA score between 1 and 4, regardless of whether the meeting was scheduled in virtual or in-person mode.…”
Section: Challenges and Outstanding Problemsmentioning
confidence: 99%
“…Literature suggests face-to-face preoperative visits for patients over 65, with significant comorbidities (e.g., diabetes), or on 7 + medications, potentially needing additional preoperative examinations after anesthesiologic evaluation [ 15 ]. Although this might suggest that patients with higher ASA score need an in-person visit, some authors found no significant differences in the rate of procedure cancellation among patients with ASA score between 1 and 4, regardless of whether the meeting was scheduled in virtual or in-person mode.…”
Section: Challenges and Outstanding Problemsmentioning
confidence: 99%